Optimization Design of a New Type of Interior Permanent Magnet Generator for Electric Vehicle Range Extender - Shilun Ma; Xueyi Zhang; Qinjun Du; Liwei Shi; Xiangyu Meng (Journal of Electrical and Computer Engineering)
Aiming at the disadvantages of large leakage flux and low magnetic flux density of radial magnetic circuit and tangential magnetic circuit, a new type of permanent magnet (PM) rotor with parallel tangential and radial magnetic circuits is proposed. Based on Ohm’s law and Kirchhoff’s law of magnetic circuits, equivalent magnetic circuits for rotor poles are developed. The structure parameters of the generator are preliminarily determined. At the same time, by means of the Taguchi method and employing finite element analysis, the rotor poles of generator are optimized to improve air gap magnetic density, the cogging torque, and the distortion of back-EMF waveform. Finally, the validity of proposed design methods is validated by the analytical and experimental results.